Krulik and Rudnick's Perspective: Analysis of Reflective Thinking Ability of Students - Muhammad Husain Isfahani, Mirza; Zuhriawan, M. Qoyum; Ashoumi, Hilyah (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Analysis of students' reflective thinking abilities in inheritance lessons from Krulik and Rudnick's perspective is a study that aims to evaluate the extent to which students are able to carry out in-depth reflection on the understanding and application of the concept of Islamic inheritance law. This approach emphasizes the importance of critical and evaluative thinking skills in the learning process, as well as how students integrate the knowledge gained with relevant practical situations. This research aims to assess the effectiveness of an interactive and personalized learning approach in improving students' reflective thinking abilities at Islamic Elementary School Fattah Hasyim. The research subjects were class IX students studying rose science. The research results show that most students are able to apply reflective thinking according to Krulik and Rudnick's steps, although there are challenges in optimizing the use of this ability. These results provide important insights for teaching strategies that can improve students' understanding and motivation to learn.